TINGKAT PEMAHAMAN GURU TERHADAP PENDEKATAN SAINTIFIK DAN IMBASNYA DALAM PENERAPAN PEMBELAJARAN DI MADRASAH TSANAWIYAH - MULIA RASYIDI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2019)
The implementation of the 2013 Curriculum in Indonesia defines several cores, namely the application of an integrated thematic learning process, using a scientific approach in learning, and authentic assessment. Some of the results of previous research on the application of the 2013 Curriculum, among others, were found that teachers who are less able to utilize resources to learn from the natural surroundings and teachers tend to maintain conventional teaching habits. From that, through this research, the researcher wants to describe how the teacher's understanding of the scientific approach; how teachers make plans for implementing learning; how the teacher applies an approach that uses science in learning, and is there a contribution between understanding the scientific approach to the application of the learning process carried out by the teacher. The research method used is the Mixed Method Research model